Kuat Tekan Beton Pofa (Palm Oil Fuel Ash) Dengan Bahan Tambah Silica Fume - Wulan Ramanda Putri; Panca Setia Utama; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Waste from processed palm oil is increasing over time. Palm Oil Fuel Ash (POFA) from boilers can be used as a substitute for cement in concrete because it contains silica and alumina. This study examines the optimum mix of cement replacement by Palm Oil Fuel Ash (POFA) and silica fume addition to the concrete mixture. The variables used are the variation of silica fume addition (0-15%) with the control concrete is PCC concrete. The concrete will be tested for its compressive strength and porosity at the age of 7 and 28 days after curing in plain water. Based on the test result, the control concrete's compressive strength was 21,74 MPa. The highest compressive strength was the concrete mixture without POFA replacement with 15% silica fume addition, the compressive strength is 26,83 MPa. It proves the addition of silica fume in concrete increases the compressive strength. Keywords: Concrete, POFA, silica fume, compressive strength.